The impact of Covid-19 on customer usage of E-Wallet in Indonesia - Ramadhan Suseto, Ramadhan; Mohamadali, Noor Azizah (Tech Science Publications, 2020)
The impact of the covid-19 pandemic greatly affected the Indonesian economy, is it predicted that the growth only reaches around 2,5%. During this time customer need to avoid physical contact with each other’s, so the only alternative is using digital transaction. The usage of e-wallet is very easy, and it is also making customer using less cash. This paper offers qualitative result of customer behavior using e-wallet in this pandemic. Nowadays people tend to use online shopping and using e-wallet as payment method rather than using cash. Even to prevent the spread of covid-19 virus the use of online shopping application surge by 300%.